Kolaborasi antara Lembaga, Masyarakat, Mahasiswa Bersama Membangun, Meningkatkan, Memperbaiki Sarana dan Prasarana Desa Gunung Karamat - Agustian, Angga; Nur Fauziah, Silvia; Resti Nuramanah; Nahla Salsabila M; Taufik Hidayat; Asep Abdul Rahman; Bayu Ramadhan; Siti Kulsum; Taufik Reifaldi; Eka Safitri (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2025)
The Community Service Program (KKN) is a form of manifestation of one of the Tri Dharma of Higher Education, namely the service carried out by students to the community which is constructive, improving and developing. This Community Service Program aims to make a real contribution in improving the quality of life of the community. The activities carried out cover several aspects, ranging from health, disaster mitigation, community empowerment, to infrastructure, and educational aspects. The purpose of this study was to determine the role of community service as part of student competency development. The implementation of KKN is expected to develop students' social competence and personality competence. The population and sample in this study were students participating in KKN and the community at the location of the implementation of KKN Students. The data collection methods used were observation, interview, and documentation. The results of this KKN activity are expected to increase public awareness of the importance of health, disaster mitigation and village potential. In addition, the infrastructure improvements made are expected to improve the quality of life of the community. Overall, this KKN program is expected to make a positive contribution to the development of Gunung Karamat Village. Keyword: The Community Service Program, Competence, Collaboration, Build ko